Print & finish - Ambrose, Gavin; Harris, Paul, 1971- (London : Fairchild Books, 2014)
"An introduction to a variety of printing and finishing techniques for any graphic design project. Now updated to include studio interviews and student activities"--
Machine generated contents note: -- IntroductionChapter one: SubstratesPaper types; Unusual substrates; Showthrough; Imposition; Tipping-in and tipping-on; Duplexing; Industry view; Activity.Chapter two: PrintingLithography and CTP; Wash printing; Silk-screen printing; Letterpress printing; Hot-metal printing; Thermography; Lino-cut printing; Industry view; Activity.Chapter three: FinishingVarnishes; Die cut; Folding; Throw outs; Gatefold; French fold; Concertina fold; Roll fold; Embossing and debossing; Foil blocking; Deckle edge; Fore-edge printing; Endpapers; Perforation; Industry view; Activity.Chapter four: ProductionRasters and vectors; Channels and plates; Print order; Overprinting techniques; Halftones; Tonal images; Tints; Industry view; Activity.Chapter five: BindingWiro, spiral and comb binding; Canadian binding; Self binds; Case binding; Perfect binding; Alternative bindings; Industry view; Activity. Chapter six: ResolveTexture; Added value; Industry view; Activity.ConclusionGlossary File format guide Folding guide Binding guide Book construction guide Index.
Keywords: Graphic design (Typography); Printing; Book design; DESIGN / Graphic Arts / General